Stanislav Shvabrin (2019). Between Rhyme and Reason: Nabokov, Translation, and Dialogue. University of Toronto Press. 440 pp. - Loison-Charles, Julie (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Book review